Hertz-Resolution Analog Quadrature Sine Oscillator. Application to Portable Lock-In Amplifiers - García Romero, Daniel; Martínez, Pedro; Calvo, Belén; Medrano, Nicolás (Jornada de Jóvenes Investigadores del I3A, 2023)
This paper presents the implementation of an analog quadrature sine oscillator capable of generating variable frequency quadrature signals, ranging from 1-100 kHz with less than 2 Hz resolution and a peak-to-peak voltage of 3 V operating at a 3.3 V single supply, to be utilized in high performance portable instrumentation.